Fatty acid and amino acid profiles in the fruits of Prunus spinosa L. subsp. dasyphylla (Schur) Domin from Europe-in- Turkey - Özcan, Tamer; Bayçu, Gülriz (İstanbul Kültür Üniversitesi, 2008)
Fatty acid and amino acid compositions were determined in the fruits of Prunus spinosa subsp. dasyphylla with GC and amino acid analyser. Total oil (0.22%) and total protein (1.35%) were quantified in lower levels. Major fatty acids were palmitic (34%), oleic (20.85%) and stearic acids (16.20%), respectively. Linoleic (6.07%), eicosatrioneic (3.17%), α-linolenic (1.95%), gamma-linolenic (1.76%), myristic (1.61%), arachidic (1.17%) and lauric acids (1.10%) exhibited the lower concentrations. The other fatty acids were examined below 1%. Total percentage of the saturated fatty acids were observed higher (56.56%) compare to the unsaturated fatty acids (35.68%). Total concentration of mono and polyunsaturated fatty acids were 22.73% and 12.95% respectively. Valuable ratio of linoleic: α-linolenic acid (3.103) were detected with respect to dietary reference for fatty acid intake. Amino acid concentrations ranged from 356.7 (aspartic acid) to 47.6 (threonin) (mg/100 g dry wt.). The highest values among essential amino acids were obtained in leucin (122.6), isoleucine (99.2), valine (87.8) and phenylalanin (84.7). Tyrosin (51.3) and lysine (50.6) were quantified at the lowest levels. All essential amino acids were observed in sufficient levels compared to FAO reference values for life stage groups. Investigated traits in the fruits of Prunus spinosa subsp. dasyphylla may be useful in explaining the natural product potential and taxonomical variations based on different populations.
Keywords: Prunus spinosa; fruit; fatty acid; amino acid; natural product; taxonomy; meyve; amino asit; taksonomi; doğal ürün; yağ asidi